How Can Talent Abroad Help Reform Institutions at Home : A Study of Russian Technological Diaspora - Freinkman, L.; Gonchar, K.; Kuznetsov, Y. (World Bank, Washington, DC, 2017)
Russia's science and technology diaspora is too visible and successful to evade attention from home. However, the public debate in Russia so far has been focused almost exclusively on return migration and on science diaspora, rather than on successful techno-entrepreneurs. The primary objective of the current Chapter is to help to refocus the debate on brain circulation facilitation of business links between high-tech entrepreneurs in diaspora and in home, and for this reason to understand better the current demand in Diaspora for stronger contacts of this kind, as well as identify the existing barriers that hamper such cross-border business contacts. Another objective of our analysis is to identify a number of success stories and key people behind such successes -- so-called overachievers in the diaspora (successful individuals in the position to share their professional success with the business community in the home country). These people may become a core of future diaspora networks that could be instrumental in upgrading the nature of Russia-diaspora cooperation. As experience of other countries suggests, such networks have a potential for supporting various Russia s initiatives in the area of innovation policy, including promotion of early stage venture capital, innovation start-ups and spin-offs.